(untitled) - Alden, John Richard (New York, 1954)
Launching a new series of encyclopedias entitled The Wars of the United States, this panoramic reference comprises some 700 detailed mini-essays on battles, campaigns, skirmishes, raids, massacres, and sea fights, along with approximately 400 biographical sketches of the leading American, British
Keywords: United States,Nước Mỹ; History,Lịch sử; Revolution, 1775-1783,Cuộc cách mạng, 1775 - 1783